PENERAPAN PEMBAGIAN HARTA WARISAN DI ANTARA AHLI WARISNYA DZAWIL FURUD MENUNJUKKAN BAHWA ANGKA PEMBILANG LEBIH BESAR DARI ANGKA PENYEBUT PASAL 192 KOMPILASI HUKUM ISLAM (KHI) - Syuhada' Syuhada' (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
Islamic inheritance, Farâ'idh or Islamic inheritance regulates various matters in the distribution of inheritance to those entitled to receive it on the basis of the provisions stipulated in the Qur'an, the sunnah of the Holy Prophet. and scholars agreement. The maker of farâ'idh or Islamic inheritance is Allah. The object is a relic. the goal can be to give heir rights to inheritance in accordance with the guidelines of Islamic law based on the Al-Qur'an, Al-Hadit, Al-?Ijmâ and Al-Qiyâs. Inheritance in Islam contains the rule of law regarding the transfer of corpses property definitively and contains a pure package from Allah SWT (tauqifi), that is why the verses of the Qur’an that explain about inheritance are not many, only three places regulate in detail, detail, and clear. Even so al-Qur'an still provides ijtihâd space in understanding the Qur'anic texts related to the explanation of inheritance law. KHI article 192